In vivo competition of delta-crystallin gene expression by DNA fragments containing a GC box. - Hayashi, S (1986)
Expression of the chicken delta-crystallin gene 1 injected into the nuclei of mouse cells is lens specific. Coinjection of GC box-containing DNA fragments from delta-crystallin, simian virus 40 early, and herpes simplex virus type 1 tk promoters effectively suppressed delta-crystallin expression in the lens, but coinjection with DNA fragments not containing the GC box did not. This suppression was likely due to the competition of an Sp1-like transcription factor(s) and indicates involvement of the apparently ubiquitous factor(s) in the tissue-specific expression of the delta-crystallin gene.